Measuring Personality in Wave I of the National Longitudinal Study of Adolescent Health - Young, J. K.; Beaujean, A. A. (Frontiers in Psychology, 2011)
The researchers sought to develop a personality measure from items in Wave I of the National Longitudinal Study of Adolescent Health. The study found 13 items from three dimensions of personality (neuroticism, extroversion, and conscientiousness), and then examined the factor structure and internal consistency of each of the three dimensions. Within each personality dimension, the items showed a unidimensional factor structure and internal consistency estimates of the summed similar to scores from NEO Personality Inventories. The results can be used to further examine how child/adolescent personality is related to multiple mental and physical health outcomes in the Add Health database.